Establishing a university records management programme: A case study of the University of Namibia (Journal for Studies in Humanities and Social Sciences, 2015)
Records management is crucial to all organizations including universities. Unless records are managed efficiently, it is not possible to conduct business effectively, and to account for what has happened in the past or to make good decisions about the future. The University of Namibia (UNAM) records management project reported in this article was carried out on the notion that records need to be systematically and continuously managed throughout their life-cycle in an integrated manner. The management of institutional records throughout their life cycle is necessary in order to support strategic business objectives of the university and to preserve corporate memory. The project was an attempt to formalize record-keeping at the university in accordance with international archival standards. Starting with information gathering, the project followed some stages which included the legal and regulatory framework, resources and staffing. The investigation also covered vital functions of the university including finance, human resources, student affairs and the executive. The information gathered using the survey method paved way for the implementation of the records management programme at the university.